ERLINDUNGAN HUKUM TERHADAP PEKERJA PENYINTAS COVID-19 ATAS PEMOTONGAN UPAH OLEH PERUSAHAAN SELAMA MENJALANI ISOLASI MANDIRI - Raudatul Adawiyah Nasution; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Implementation of legal protection for wages of workers/laborers in employmentrelations is urgently needed, bearing in mind that the socio-economic position ofworkers/laborers is very weak, especially during the Covid 19 pandemic. Manycompanies have ignored workers' rights, including the fulfillment of wages whileundergoing self-isolation which means workers are in the process of healing whose rightsare protected under the provisions of Article 40 of Government Regulation Number 36 of2021 concerning Wages which mandates that every worker/laborer who does not workdue to illness, his wages are still paid in full.This research is classified as a sociological research type, because it directlyconducts research on the locations or points examined to provide a complete and clearpicture of the problems examined. This research was conducted in Pekanbaru City withsources from the Riau Province Manpower and Transmigration Office, while the samplepopulation was Covid-19 survivors who experienced wage deductions while undergoingindependent isolation. Sources of data used, primary data and secondary data, datacollection techniques in this study by interviews, literature review, and data analysis.The results of this study are as follows: First, that the implementation of legalprotection against wage deductions experienced by workers who are survivors of Covid19byemployersinseveralcasesinPekanbaruhasnotbeenfulfilledinaccordancewiththeprovisions of Article 40 of Government Regulation Number 36 of 2021 concerningWages. In practice, 8 out of 21 employers have deducted survivor workers' wages fromthe basic wages, because workers undergo independent isolation for 15 days. Second,efforts to resolve disputes between workers and employers can be carried out throughbipartite negotiations. If viewed from the concept of dispute resolution theory,negotiations must proceed equally, must not proceed as normal internal negotiations bynot considering the condition of workers who experience illness. It is necessary to beaware that employers/employers and workers in implementing work agreements must bein accordance with legal protection based on Article 40 of the Government Regulation onWages which mandates that every worker/laborer who is not working due to illness, hiswages must still be paid in full and understand the concept of dispute resolution and thebipartite negotiation mechanism in accordance with the provisions of Article 6 of LawNumber 2 of 2004 concerning the Settlement of Industrial Relations Disputes also inorder to produce mutually beneficial agreements for both parties, in particular workersmust join a trade union.